Australian History World Wide Web Project. - Turnbull, Paul ([James Cook University], 1998)
This is a final report for a 1996-1998 National Teaching Development Grant funded by the Committee for University Teaching and Staff Development. The objective of this still evolving project has been to appraise the potential of web-based teaching and learning in history. It entails the construction of five interactive learning modules focused on key aspects of the social history of health in Australia, supported by a range of virtual resources, including a virtual library and integrated on-line tutorial facilities. The report details the History project and provides justification and educational rationale for its development.